1-Hexyl n-cyanoacrylate compound (Neucrylate™ AN), a new treatment for berry aneurysm. III: Initial clinical results. (23rd June 2011) - Pakbaz, R S; Shakiba, M; Ghanaati, H; Akhlaghpoor, S; Shakourirad, A; Kerber, C W
Abstract : Introduction: As part of an institutionally approved research protocol, patients with cerebral berry aneurysm were enrolled in a clinical trial designed to evaluate the safety of the new moldable liquid embolic agent Neucrylate AN. Methods: Twelve patients with aneurysms judged to be suboptimal for treatment by standard endovascular or surgical approaches were treated with Neucrylate AN. The agent was injected during temporary balloon occlusion at the neck of the aneurysm. The immediate angiographic percentage of aneurysm occlusion and periprocedural adverse events were assessed for each patient. Six-month follow-up angiographic studies were obtained for nine of the 12 patients. Results: Ten of the 12 aneurysms treated (83%) were large to giant (>1.0 cm in diameter), nine (75%) were wide-necked (dome/neck ratio <2.0) and three (25%) were dissecting aneurysms. There were four (33%) periprocedural neurological events. Immediate aneurysm occlusion of >90% was obtained in nine of the 12 cases (75%). There were five recurrences (55.5%) at 6 months. Conclusion: This preliminary clinical series shows that it is feasible to achieve a high percentage of immediate aneurysm occlusion with limited patient morbidity and mortality in the setting of morphologically challenging aneurysms. These preliminary data support larger trials assessing the safety and efficacy of this agent.